Concurrent Nab-paclitaxel and Radiotherapy: Novel Radiosensitization for Borderline Resectable or Unresectable Pancreatic Cancer. (September 2021) - Arscott, William T.; Nead, Kevin T.; Bear, Adham; Venigalla, Sriram; Shabason, Jacob; Lukens, John N.; Plastaras, John P.; Wojcieszynski, Andrzej; Metz, James; O'Hara, Mark; Reiss, Kim A.; Teitelbaum, Ursina; et al.
Abstract : Purpose: This study evaluates the toxicity and tumor response with concurrent nab-paclitaxel chemoradiotherapy (CRT) compared with standard (5-fluorouracil or gemcitabine) CRT. Materials and Methods: Fifty patients with borderline resectable or unresectable pancreatic adenocarcinoma from 2014 to 2017 were divided into 2 groups: concurrent nab-paclitaxel (100 to 125 mg/m 2 weekly) CRT (median: 2.1 Gy fraction size and 52.5 Gy total) or standard CRT (median: 1.8 Gy fraction size, 54.5 Gy total). The primary endpoint was toxicity, and secondary endpoints were local failure and conversion to resectability. Comparisons were made using rank-sum or Fisher exact test and multivariable competing risk regression for the cumulative incidence of local failure. Results: There were 28 patients in the nab-paclitaxel CRT group and 22 in the standard CRT group; 88% had the unresectable disease. The median follow-up was 18 months. The median duration of chemotherapy before concurrent CRT was 1.9 and 2.3 months in the nab-paclitaxel and standard CRT groups ( P =0.337), and radiotherapy dose was 52.5 Gy (range, 52.5 to 59.4 Gy) and 54.5 Gy (range, 45.0 to 59.4 Gy), respectively. There were no statistically significant grade ≥2 toxicities. The nab-paclitaxel CRT group experienced a nonstatistically significant lower incidence of local failure (hazard ratio=0.91, 95% confidence interval: 0.27-3.03, P =0.536). More patients in the nab-paclitaxel CRT group proceeded to surgery (9/28 compared with 3/22 in the standard CRT, P =0.186); of which 6 (25%) in the nab-paclitaxel CRT and 2 (10%) in the standard CRT groups were initially unresectable. Conclusions: Nab-paclitaxel CRT had similar toxicity compared with standard CRT in the treatment of borderline resectable or unresectable pancreatic cancer. Its use was associated with an arithmetically lower cumulative incidence of local failure and an arithmetically higher conversion to resectability, both of which were not statistically significant.